The Effect of Using a Camouflaged Dental Syringe on Children’s Anxiety and Behavioral Pain: A Comparative Study - Dr. Nishith M Shah; Dr. Anurag Thakuria; Dr. Kanchan Sharma; Dr. Sumit Bhatt; Dr. T. Hemalatha; Dr. Soundarya Vishwanathan (The Bioscan, 2025)
Aim: The investigation aims to determine the positive effectiveness of customised camouflaged syringes instead of traditional ones on the children's behavior and anxiety levels. Materials and methods: 40 children between the ages of 4-10 participated in the research; they were allocated into two groups: group 1 (4–7 years) and group 2 (7–10 years). The first session used conventional syringes, while the second session used a specially designed camouflage syringe which utilized a split-mouth design in group 1 and vice versa in group 2. An anesthetic gel was given topically before the block was administered. Using the FLACC (Face, Legs, Activity, Cry, Consolability) scale behavior pain was assessed while local anesthetic (LA) was being administered. The children's degree of anxiety was expressed by the children using the Chotta Bheem–Chutki (CBC) pictorial scale after the block delivery. The samples were compared for significant differences (p < 0.05) using the Mann-Whitney U test. Results: Although there was no discernible difference in groups and gender, children's behavior was positively impacted by camouflaged syringes, which dramatically score lesser FLACC pain scale score and decreased anxiety on the CBC scale during LA. Conclusion: Children's conduct is positively impacted by camouflaged syringes. They effectively lower anxiety levels by increasing distraction.